The Effect of Project-Based Learning Method on Understanding Geometry Concepts in Secondary School Students - Trio Putra Siregar (Attractive : Innovative Education Journal, 2024)
This study aims to analyse the effect of project-based learning (PBL) method on the understanding of geometry concepts in secondary school students. The main focus of the research is to understand how the application of PBL can help students overcome difficulties in understanding abstract geometry concepts, while improving critical thinking and collaboration skills. This research uses the literature study method by reviewing various scientific journals, books, and relevant articles that discuss the effectiveness of PBL in teaching geometry. This research method involves collecting, analysing, and synthesising previous research results to identify trends, successes, and challenges in the implementation of PBL. The results show that PBL is able to create a more interactive and contextualised learning environment, which allows students to connect geometry theory with practical applications through projects such as geometric model making, building design, or analysis of geometric shapes in everyday life. PBL is an effective method to improve the understanding of geometry concepts in secondary school students. This approach not only enriches students' learning experience but also helps them develop 21st century skills, such as problem solving and teamwork. The implications of this study underline the importance of training for educators as well as the provision of supporting facilities to maximise the potential of PBL in teaching geometry.